Highlighting the Major Trade-Offs Concerning Anti-Terrorism Policies - Olaf J. de Groot; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Human-induced security, or terrorism, is a threat to wellbeing in Europe and beyond. In this Policy Briefing, we investigate the risks involved in terrorism, both with respect to the likelihood and with respect to the consequences of acts of terrorism. Furthermore, we provide a basic analysis of existing anti-terrorism policies, the costs involved in them and their effectiveness. We show that terrorism is a very broad term, but that one can make a number of broad policy recommendations, including the fact that the rational economic approach to terrorism recognizes that terrorists respond to the incentives they are provided with.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330